PROBLEMATIQUE DES PRATIQUES DES STRATEGIES MANAGERIALES DANS LA VENTE DE PRODUITS DE LA GLOBAL MARKET MOVERS SUR LE MARCHE CONCURRENTIEL D’ISIRO DE 2013 A 2017. - Jean-Luc BANAMBEANISO OPANA, (IJRDO - Journal of Business Management, 2019)
The present investigation relating to the problems of the practices of the strategies manageriales  in the sale of products of Total Market Movers (GMM) on the competitive market of Isiro of 2013 to 2017.¶It has as a major concern to know if Company GMM in general, the deposit of Isiro in particular uses the strategies manageriales in its commercial deals and so yes to show the incidence of the aforementioned strategy on the general tendency of the sales of its product "Supermatch" on a purely competing market like that of matter Isiro of the cigarettes.¶¶We thus wanted to in general determine the level of competitiveness of company GMM in democratic Republic of Congo, particularly downtown of Isiro